Topsoil Bacterial Community Changes and Nutrient Dynamics Under Cereal Based Climate-Smart Agri-Food Systems - Choudhary, Madhu; Jat, Hanuman S.; Datta, Ashim; Sharma, Parbodh C.; Rajashekar, Balaji; Jat, Mangi L. (Frontiers in Microbiology, 2020)
Soil microorganisms play a critical role in soil biogeochemical processes, nutrient cycling and resilience of agri-food systems and are immensely influenced by agronomic management practices. Understanding soil bacterial community and nutrient dynamics under contrasting management practices is of utmost importance for building climate-smart agri-food systems. Soil samples were collected at 0-15cm soil depth from six management scenarios in long-term conservation agriculture (CA) and climate smart agriculture (CSA) practices. These scenarios (Sc) involved; ScI-conventional tillage based rice-wheat rotation, ScII- partial CA based rice-wheat-mungbean, ScIII- partial CSA based rice-wheat-mungbean, ScIV is partial CSA based maize-wheat-mungbean, ScV and ScVI are CSA based scenarios, were similar to ScIII and ScIV respectively, layered with precision water & nutrient management. The sequencing of soil DNA results revealed that across six scenarios, a total of forty bacterial phyla were observed with Proteobacteria as dominant in all scenarios followed by Acidobacteria and Actinobacteria. The relative abundance of Proteobacteria was 29% higher in rice based CSA scenarios (ScIII and ScV) and 16% higher in maize based scenarios (ScIV and ScVI) compared to ScI. Relative abundance of Acidobacteria and Actinobacteria was respectively 29% and 91% higher in CT than CSA based rice and 27% and 110% higher than maize based scenarios. Some taxa are present relatively in very low abundance or exclusively in some scenarios, but these play important role there. Three phyla are exclusively present in ScI and ScII i.e. Spirochaetes, Thermi, and Euryarchaeota. Shannon diversity index was 11% higher in CT compared to CSA scenarios. Maize based CSA scenarios recorded higher diversity indices than rice-based CSA scenarios. After nine years of continuous cropping, the soil organic carbon was improved by 111% and 31% in CSA and CA scenarios over CT scenario. Similarly, the available nitrogen, phosphorus, and potassium were improved by respectively 38%, 70%, and 59% in CSA scenarios compared to CT scenario. These results indicate that CSA based management has positive influence on soil resilience in terms of relative abundances of bacterial groups, soil organic carbon & available plant nutrients and hence may play critical role in sustainability of the intensive cereal based agri-food systems.